2002
DOI: 10.1017/s1431927602105289
|View full text |Cite
|
Sign up to set email alerts
|

Atomic imaging in aberration-corrected HRTEM with application to Al alloys

Abstract: Since the successful correction of the spherical aberration (Cs) of the objective lens in a Philips CM 200 FEG ST microscope achieved by Rose and Haider et al [1][2], a few theoretical and computational expectations have been made to show the possible atomic imaging conditions in the Cs-corrected high-resolution transmission electron microscopy (HRTEM) [3][4]. These conditions include the phase-contrast imaging at a small defocus, the amplitude-contrast imaging at about zero defocus and the projected charge de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…These conditions include the conventional phase-contrast imaging at a small defocus [5], the projected charge density (PCD) contrast imaging at a small over-focus [5,7], and the amplitude-contrast imaging at about zero defocus [6,[8][9]. And very recently, it has been demonstrated that the images obtained at a small negative Cs (-40 mm) and correspondingly at an over-focus (+8 nm) also reflect the atomic structures of the materials [10][11].…”
Section: Direct Atomic Imaging In the Aberrationcorrected Hrtemmentioning
confidence: 99%
See 4 more Smart Citations
“…These conditions include the conventional phase-contrast imaging at a small defocus [5], the projected charge density (PCD) contrast imaging at a small over-focus [5,7], and the amplitude-contrast imaging at about zero defocus [6,[8][9]. And very recently, it has been demonstrated that the images obtained at a small negative Cs (-40 mm) and correspondingly at an over-focus (+8 nm) also reflect the atomic structures of the materials [10][11].…”
Section: Direct Atomic Imaging In the Aberrationcorrected Hrtemmentioning
confidence: 99%
“…In an aberration-corrected HRTEM, Cs will be small (0-40 mm) [4][5][6][7][8][9][10][11], so the optimum defocus values for obtaining the interpretable atomic images will be around À7.5 nm [5][6][7][8][9][10][11]. Fig.…”
Section: Phase-contrast Imagingmentioning
confidence: 99%
See 3 more Smart Citations